Adult education as care work in a South African prison: the role of adult educators - Doria Daniels (Perspectives in Education, 2013)
The 2000s saw a change in South Africa’s Department of Correctional Services’ theorising about adult education’s potential to shift incarcerated men’s thinking about their future in a proactive way. The plan was to advance active citizenship in the incarcerated. As such, the Department of Correctional Services (DCS) introduced holistic, integrated adult educational programmes at twelve of its prisons. Although the policy and scaffolding aspects of AET (Adult Education and Training) received extensive attention, limited research was done to understand the situational and institutional challenges that adult learning centres are presented with, and how institutional culture impacts on the successful implementation of policy. The contributions that adult educators make in advancing transformative learning in adult learning centres, often go unacknowledged because they are seldom the focus of educational research.